Hepatoprotective effect of andrographolide on paracatemol induced liver damage in BALB/C mice - Mohd Yusof, Norhasimah (2015)
Andrographis Paniculata has been widely used as hepatoprotectant for liver damage problem. The active compound called andrographolide is reported to be hepatoprotective and its protection against paracetamol-induced was better than that produced by silybin. In this study, the in vivo hepatoprotective effect and antioxidant effect of andrographolide were determined by comparing with the untreated and silybin (positive control) groups. Liver superoxide dismutase (SOD), malondialdehyde (MDA), ferric reducing antioxidant power (FRAP), nitric oxide (NO) levels, and serum biochemical profile including aspartate transaminase (AST),alanine transaminase (ALT), alkaline phosphatase (ALP), Total Bilirubin (TBil), triglycerides (TG), and cholesterol, also serum IL-2 and IFN- γ levels, immunophenotyping evaluation and histopathological changes were studied. Results showed that the serum enzyme biomarker levels were reduced in the paracetamol-induced mice after administration of 200 μL andrographolide extract (30mg/kg).These serum levels are including ALT (P=0.0012), AST (P=0.0011), TG (P=0.0079),Chol (P=0.0053), and TBil (P= 0.0012). Besides, comparing to silybin, the liver antioxidant levels such as SOD (P<0.0001) and FRAP were restored and the reduction of NO (P=0.0105) and MDA (P=0.0005) in the liver andrographolide treated mice were also seen. In conclusion, andrographolide was capable of recovering the damaged hepatocytes to their normal structures hence could enhance hepatoprotective and antioxidant effects in vivo of paracetamol-induced hepatotoxicity.